Simulasi Model Jaringan dan Fasilitas Permukaan Injeksi CO2 Sistem Terpusat pada Lapisan F Lapangan J - Yulius Deddy Hermawan; wibowo wibowo (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2013)
The Study of CO2 injection to enhance oil recovery through several stages before implementation on the pilot and full scale projects in the field had been done succesfully. The final stage of this study has been made by modeling of network and CO2 injection surface facilities that can be implemented in J Field. The developed model which is run by production simulator gave significant results both on the re-pressurized stage and CO2 flooding stage. This study showed that the implementation of CO2 injection could be run well. With the model validation through static and dynamic run, this study also reavealed that the network model and surface facilities could work properly.